Cognitive Decline After Surgery and Anaesthesia: Correlation Does Not Mean Causation. Issue 1 (February 2017) - Docherty, A. B.; Shenkin, S. D.
Abstract : (Abstracted from Anaesthesia, 71(10):1131–1135, 2016) Postoperative cognitive dysfunction is a transient alteration in cognitive function, including memory, information processing, and executive function, lasting a few days to as long as a few weeks after surgery. There is an increasing concern about the potential impact of surgery on the cognitive ability in older people undergoing surgery.